Play and the human condition - Henricks, Thomas S. (University of Illinois Press, 2015)
Thomas S. Henricks brings together ways of considering play to probe its essential relationship to work, ritual and communitas. Focusing on five contexts for play - the psyche, the body, the environment, society and culture - Henricks identifies conditions that instigate play, and comments on its implications for those settings.